Eficiencia térmica en sistema de protección solar para el clima cálido húmedo. Caso de estudio: edificio Serfinanza, Barranquilla. (2021)
The buildings have been remodeled to the modernist trend of glazed facades, which are causing thermal discomfort in the interior for which they resort to the implementation of mechanical ventilation mechanisms to satisfy the thermal comfort in the interior. In the present work, it’s intended to evaluate the influence on the interior thermal behavior with a solar protection design in a building for business use in the city of Barranquilla, which is descriptive - experimental, in which by searching for factors to Through the manipulation of variables, in digital simulations where different existing theoretical information is integrated, organized and evaluated based on the problems already exposed, the impact of radiation from glazed facades and responding to the study objectives, therefore, a solution was generated experimental type design in solar protection, the façade exposed to solar radiation was analyzed for the incidence of the solar angle so that the solar protection could be tilted so that the direct radiation intersects, reducing the interior temperature in a maximum delta of 2.6 ° C, the solar protection is designed in the materiality of steel being thus compared with the materiality of concrete. to 2.7 times lighter providing less dead load to buildings already built.